PENGARUH LAYANAN INFORMASI BIDANG BIMBINGAN SOSIAL TERHADAP PERKEMBANGAN PERILAKU SOSIAL SISWA - Bahri, Syamsul; Alam, Andi Aminullah; Supiati, Supiati (STKIP Andi Matappa, 2017)
The purpose of this study is: To determine the effect of information services in the field of social guidance promote the development of social behavior Students of Class X in SMK 1 Minasatene. This research uses experimental approach, where a population of 141 students and a sample of 30 students from the population with the sampling technique is purposive random sampling or sampling purposel technique. The data collection technique using questionnaire instrument that has been tested for validity and reliabelitasnya and documentation. Analyzed using descriptive statistics and inferential statistical analysis, the t-test. The results showed that: the provision of social assistance field information services making a positive impact in improving the behavioral development of students of Class X in Smk Negeri 1 Minasatene after a given social assistance field of information services